Pengaruh Alat Permainan Edukatif Alphabetic Puzzle Terhadap Kemampuan Membaca Permulaan Anak Kelompok A Di B.A Aisyiyah Sonorejo II Sukoharjo Tahun Ajaran 2016/2017 - Hidayah, Ummul, Dra. Surtikanti, S.H, M.Pd (2017)
The purpose of the research is to determine the education game toys of alphabetic puzzle toword the pre reading ability of group A at B.A Aisyiyah Sonorejo II Sukoharjo Academic Year 2016/2017. The method of the research was quantitative method there are using a kind of experimental research with pre-eksperimental research design is using one group pretest-posttest design. This research was conducted in February the object was 27 childern. The data collection techniques of the research were conducted through observastion, there are participant observation, documentation and interview. The data were analysed techniques of the research using ttest with SPSS 16.0 for windows. The results of data analysis using ttest obtained ttest -10.094 < -ttable -1.7056 so H0 is rejected and Ha is accepted wich there influance of education game toys of Alphabetic Puzzle to ward the pre reading ability Keyword: Tool Educative Game Alphabetic Puzzle, early reading ability